Effect of Fertilizer Levels on Fodder Productivity and Quality of Multi-cut Sorghum Genotypes - Yadav, Kiran; Verma, Arvind; Yadav, Mukesh Kumar; Choudhary, Mukesh; Choudhary, Kesar Mal (International Journal of Bio-resource and Stress Management, 2019)
A field experiment was conducted at Udaipur (Rajasthan) to study the effect of fertility levels on productivity and quality of multi-cut forage sorghum genotypes. The experiment was laid out in a randomized block design with 3 replications. The treatments consisted of seven multi-cut forage sorghum genotypes (SPV 2242, SPH 1700, SSG 59-3, CSH 20 MF, CSH 24 MF, MP Chari and CoFS-29) and four fertility levels viz., 50, 75, 100 and 125% recommended dose of fertilizers (RDF). Result showed that multi-cut forage sorghum genotype SPH 1700 produced highest green (58.08 t ha-1) and dry fodder (17.97 t ha-1) yield in first cut, however genotype CoFS-29 produced highest green and dry fodder yield in second cut. Maximum crude protein yield was recorded in CoFS-29 (2017 kg ha-1) followed by SPH 1700. Similarly, total digestible nutrients (sum of both cuts) was recorded in CoFS-29 (13.0 t ha-1) followed by SPV 2242 and least in MP Chari (11.13 t ha-1). Among fertilizer levels, application of 125% RDF increased green and dry fodder yield by 8.8 and 9.6% over 100% RDF. Graded application of fertilizer also improved quality of fodder in terms of crude protein, ether extract and mineral ash resulted highest total digestible nutrients (14.1 tha-1) under 125% RDF. Findings of our study shows that growing of sorghum multi-cut variety ‘CoFS-29’ with application of 125% RDF (100 kg N and 50 kg P2O5 and 50 kg K2O ha-1) improved fodder production and their quality.